Pengaruh Pemberian Kompensasi terhadap Kinerja Karyawan Hotel Dafam Kota Pekalongan - Aria Mulyapradana; Tri Rosewati; Farikhul Muafiq (Widya Cipta - Jurnal Sekretari dan Manajemen, 2020)
Abstract: Competition in the increasingly stringent era of globalization companies are required to be able to win business competition with a healthy. The success of a company is determined by the extent to which leaders create and produce good employee performance to achieve predetermined goals. Providing compensation is an activity to improve employee performance. Satisfaction with compensation given by the company can influence employees to work more enthusiastically to achieve company goals. The purpose of this study was to examine the effect of giving compensation to employee performance in Dafam Hotel, Pekalongan City. The method used is a quantitative method using SPSS version 16.0 and data collection methods by observation, interviews and distributing questionnaires to employees of the Dafam Hotel in Pekalongan City with a total of 44 respondents using census techniques. Data collection techniques using a questionnaire with a Likert scale, each of which has been tested using validity and reliability. Analysis of the data used simple linear regression analysis and hypothesis testing using the t test can be concluded that there is a real effect between the provision of compensation on employee performance in the Dafam Hotel, Pekalongan City. Keywords: compensation, performance, employees and hotel